Caracterização física e fisiológica de sementes de jiló (Solanum gilo) em diferentes estádios de desenvolvimento - Alves, Marcus Vinicius Prado (2016)
The evaluation of seed quality during the development process is important to the harvest time definition. In this context, the objective of this study was to evaluate the quality of eggplant seeds during their development through physiological tests, enzymes electrophoretic pattern and analysis seed images. Six genetic materials were used, white JIL, JIL 001 JIL 005 JIL 006, H1 and H2. Fruits were harvested at 35, 40, 45 days after anthesis (DAA) and fruits harvested at 45 DAA and which stayed at rest for seven days (45DAAr). The in each maturity stage seeds were extracted from fruits and evaluated for water content, thousand seed weight, electrical conductivity, root protrusion, root protrusion velocity index, germination, germination speed index, seedlings emergency, emergency speed index seedlings, seedlings fresh and dry weight. The the seeds chemical compositions also evaluated. As well as the expression of esterase (EST), isocitrate lyase (ISO) malate dehydrogenase (MDH), alcohol dehydrogenase (ADH), superoxide dismutase (SOD), catalase (CAT), horseradish peroxidase (PO) and endo-β- mannanase . The seeds image analysis was done by means of X-rays with the help of software ImageJ®. The highest germination and vigor values were observed in seeds harvested at 45 DAA and 45 DAAr. The eggplant seeds expression of the endo-β-mananse enzyme increased as the advance of maturity stage. The eggplant seeds advanced radiographic image analysis with the help of software ImageJ® allowed the measurement the free internal areas at different stages of maturation.